Paclitaxel coated balloon fibroplasty: A more effective treatment for chronic symptomatic lead/catheter related central venous obstruction?. (5th February 2021) - Yacob, Omar; Worley, Seth; Brar, Vijaywant; Towheed, Arooge; Hadadi, Cyrus; O'Donoghue, Susan
Abstract: Central venous occlusion is a common complication following transvenous lead or therapeutic catheter placement that can present either acutely or chronically. KEY TEACHING POINTS: Lead related chronic fibrotic venous obstruction can occasionally be highly symptomatic. Fibroplasty (AKA venoplasty) is a safe option that provides immediate relief, however, symptoms frequently recur presumably due to restenosis. Drug coated balloons reduce restenosis in dialysis fistulas and may improve the long‐term results in symptomatic patients with lead/catheter related chronic venous obstruction.